HAMBATAN BELAJAR MAHASISWA PADA MATA KULIAH PSDK JURUSANKESEJAHTERAAN KELUARGA FAKULTAS TEKNIK UNIVERSITAS NEGERI PADANG - Morjayanti, Novi Adi; Elida, Elida; Syarif, Wirnelis (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2013)
The aims of this research are to describe the resistance in planning before follow PSDK,the resistance in doing PSDK, and the resistance in evaluating after follow PSDK. The kind of this research is qualitative descriptive. The informants in this research are all PKK FT UNP students who have taken PSDK (53 students), and also the PSDK lecturer (1 person). Data collection by observation, interview and questionnaire. Depends on the result, the resistances are in planning the daily menu that don’t have various shape, taste and colour. And the use of the food material that too various, so there are some of them that can’t be found in the market, the resistance in doing PSDK in managing the resources in both of cookery and fashion major, the lack of the facilitation, and the resistances in evaluating and make the finance report, that there are some profits that is not reported because it have been taken for the next business. Keywords: Difficulties in studies, PSDK subject, Kesejahteraan Keluarga Department.